PENGARUH BEBAN KERJA DAN KEPEMIMPINAN TERHADAP KINERJA KARYAWAN PADA CV. HERRIS TRADING KOTA TANGERANG - Desi Prasetiyani (SCIENTIFIC JOURNAL OF REFLECTION : Economic, Accounting, Management and Business, 2023)
This study aims to determine the influence of workload and leadership on employee performance on CV Herris Trading Kota Tangerang both partially and simultaneously. This type of research uses quantitative descriptive methods. The population was 85 with saturated sampling techniques and the sample in this study amounted to 85 respondents. Data analysis uses regression analysis, correlation coefficient analysis, determination coefficient analysis and hypothesis testing. The results showed that workload had a significant effect on employee performance with a regression coefficient of 0.553, meaning that there was a significant influence between workload and employee performance. Leadership has a significant effect on employee performance with an estimated value of 0.476, meaning that there is a significant influence between leadership and employee performance. Workload and leadership have a significant effect on employee performance with the regression equation Y = 16.161 + 0.331X1 + 0.244X2. A correlation coefficient of 0.740 means that the independent variable and the dependent variable have a strong relationship level with a coefficient of determination of 54.8%